“Feeding healthy, good and cheap”. The Restaurantes Populares in Santiago de Chile (1936-1942) - Yáñez Andrade, Juan Carlos (Cuadernos de Historia, 2016)
This article studies the unreleased experience of the restaurantes populares in Santiago of Chile, in the context of the debates for the rising in the cost of living and the formulation of the food policy for workers during the 1930s. Using varied sources there are analyzed the objectives of the restaurantes populares, especially in offering a nourishing food and to low cost, and the discussions that it generated in the political context of the period.